"Anger Detracts From Beauty": Gender Differences in Adolescents' Narratives About Anger. Issue 5 (September 2020) - Budziszewska, Magdalena; Hansen, Karolina
In a mixed-design narrative study, we explore how adolescent boys and girls represent experiences of anger and how their narrations are linked to self-esteem and anxiety. Polish teens from three nonurban public schools ( N = 101, 55% female, M age = 15.5) wrote narrative accounts of their typical anger experience. We use a thematic analysis framework to analyze the patterns in these narratives. Boys and girls told stories within school, family, and relationship contexts. However, boys provided more stories that focused on the theme of everyday incidental instances of anger, whereas girls provided more stories focused on the theme of negative inner experiences. In-depth analysis resulted in the emergence of two complex narrative patterns: Anger as Outburst and Anger as Burden . Anger as Outburst described heated anger related to difficulties in self-control and aggression and was more characteristic of boys. Anger as Burden contained stories of prolonged anger related to negative self-evaluation and was more characteristic of girls. Anger as Burden was also related to higher anxiety and lower self-esteem. We conclude that in the given cultural context, adolescents lack positive narratives to frame their anger adaptively.